Review On Effect Of Heat Input For Wire Arc Additive Manufacturing Process - Alkahari, Mohd Rizal; Abdollah, Mohd Fadzli; Ramli, Faiz Redza; Rosli, Nor Ana; Maidin, Shajahan; Herawan, Safarudin Gazali (Elsevier Editora Ltda, 2021)
Wire arc additive manufacturing (WAAM) is steadily increasing with significant research work are underway. The ability of WAAM to manufacture a large-scale product at a lower cost and shorter lead times has increased its development. The efficiency or potential of WAAM to become a new lead in the additive manufacturing industry is believed to be realized by a few factors. High efficiency and performance require a higher metal deposition rate, which implies higher heat input that negatively affects the manufacturing process. This paper review works for factors associated with heat input on the WAAM process. The factor affecting these properties were explained to identify the optimized WAAM process in terms of heat input. The paper focuses on the impact of heat input on the macrostructure, microstructure and mechanical properties of the parts deposited in the WAAM process. This review also discussed the effect of heat input used by eight different types of arc welding technologies, with appropriate use of wire materials. The study also highlights that heat input affected the microstructure of the WAAM, causing significant changes in grain structure, grain size and pore area percentage. Besides, it can be suggested that grain structure has a strong influence on the WAAM materials' mechanical properties.